Balance training with multi-task exercises improves fall-related self-efficacy, gait, balance performance and physical function in older adults with osteoporosis: a randomized controlled trial. (April 2015) - Halvarsson, Alexandra; Franzén, Erika; Ståhle, Agneta
Objective: To evaluate the effects of a balance training program including dual- and multi-task exercises on fall-related self-efficacy, fear of falling, gait and balance performance, and physical function in older adults with osteoporosis with an increased risk of falling and to evaluate whether additional physical activity would further improve the effects. Design: Randomized controlled trial, including three groups: two intervention groups (Training, or Training+Physical activity) and one Control group, with a 12-week follow-up. Setting: Stockholm County, Sweden. Participants: Ninety-six older adults, aged 66-87, with verified osteoporosis. Interventions: A specific and progressive balance training program including dual- and multi-task three times/week for 12 weeks, and physical activity for 30 minutes, three times/week. Main measures: Fall-related self-efficacy (Falls Efficacy Scale-International), fear of falling (single-item question – 'In general, are you afraid of falling?'), gait speed with and without a cognitive dual-task at preferred pace and fast walking (GAITRite®), balance performance tests (one-leg stance, and modified figure of eight), and physical function (Late-Life Function and Disability Instrument). Results: Both intervention groups significantly improved their fall-related self-efficacy as compared to the controls ( p ≤ 0.034, 4 points) and improved their balance performance. Significant differences over time and between groups in favour of the intervention groups were found for walking speed with a dual-task ( p =0.003), at fast walking speed ( p =0.008), and for advanced lower extremity physical function ( p =0.034). Conclusions: This balance training program, including dual- and multi-task, improves fall-related self-efficacy, gait speed, balance performance, and physical function in older adults with osteoporosis.